Detecting overweight and obesity among young Syrian boys based on skinfold thickness - Al-Bachir, Mahfouz; Ahhmad, Hussam (Anthropological Review, 2016)
There is no data on the prevalence of overweight and obesity in young Syrian boys. Therefore, the present study aimed to provide baseline and reference data on the prevalence of overweight and obesity among young Syrian boys using skin-fold thickness measurements and deuterium dilution (DD) as a reference method. The sample of 2470 healthy Syrian 18- to 19-year-old boys were enrolled in this study. SFTs were measured at the biceps (B), triceps (T), subscapular (SI) and suprailiac locations (SS) were done and validated using the DD technique as a reference method. Receiver operating characteristics (ROC) curve was drawn to determine appropriate cut-off points of the Σ2 limb SFT (T+B), Σ2 trunk SFT (SI+SS), Σ4 SFT (T+B+SI+SS) and Log Σ4 SFT for defining overweight and obesity. The overall prevalence of overweight and obesity in young Syrian boys, based on biceps SFT, triceps SFT, subscapular SFT, suprailiac SFT, Σ2 limb SFT, Σ2 trunk SFT, Σ4 SFT, logarithm Σ4 SFT, and DDT were 35.3%, 32%, 31.6%, 14.8%, 32.9%, 26.6%, 28.1%, 24.1%, 46.5%, respectively. Strongly positive correlation was found between SFT and total body fat in adolescents. For diagnosing overweight on the basis of Σ2 limb SFT, Σ2 trunk SFT, Σ4 SFT and logarithm Σ4 SFT, we propose the following cut-off points: 17.25 mm, 23.50 mm, 39.25 mm and 1.60, respectively. To predict obesity, Σ2 limb SFT, Σ2 trunk SFT, Σ4 SFT and logarithm Σ4 SFT threshold were increased to 23.25 mm, 32.50 mm, 55.25 and 1.75, respectively. Basing on SFT clearly leads to underestimates of the prevalence of weight problems among young boys. SFT measurement screen missed 11.2 to 31.7% of overall overweight and obesity cases.